Care to Dare : Unleashing Astonishing Potential Through Secure Base Leadership. - Kohlrieser, George (John Wiley & Sons, 2012)
Have you ever been led by someone who cared for you like family, and dared you to achieve more than you ever thought possible for yourself, your organization, and even society?Award-winning author of Hostage at the Table, George Kohlrieser, along withḧisÈco-authors Susan Goldsworthy and Duncan Coombe, ëxplainhow becoming a secure base leader releases extraordinary potential in others. Part of the Warren Bennis leadership series Care to Dare shows you how to become a Secure Base Leader so that you release your followers from the fears that get in the way of their performance. It.